Developmental Characteristics and Auxin Response of Epiphytic Root in Dendrobium catenatum - Tian, Jili; Jiang, Weiwei; Si, Jinping; Han, Zhigang; Li, Cong; Chen, Donghong (Frontiers in Plant Science, 2022)
Dendrobium catenatum, a traditional precious Chinese herbal medicine, belongs to epiphytic orchids. Its special life mode leads to the specialization of roots, but there is a lack of systematic research. The aerial root in D. catenatum displays diverse unique biological characteristics, such as multi-layered spongy velamen, highly developed exodermis, underdeveloped root cap, etc. The root initially occurs in the form of adventitious root, which endogenously originates from the opposite pole of the shoot meristem of the protocorm. The root development of D. catenatum is not only regulated by internal cues but also adjusts accordingly with the change of growth environments. D. catenatum root is highly tolerant to auxin, which may be closely related to its epiphytic life. Exogenous auxin treatment has dual effects on D. catenatum roots: relatively low concentration promotes root elongation, which is related to the induced expression of cell wall synthesis genes; excessive concentration inhibits the differentiation of velamen and exodermis and promotes the excessive proliferation of cortical cells, which is related to the significant upregulation of WOX11-WOX5 regeneration pathway genes and cell division regulatory genes. Overexpression of D. catenatum DcWOX12 in Arabidopsis inhibits cell and organ differentiation, but induces cell dedifferentiation and callus production. Therefore, DcWOX12 not only retains the characteristics of ancestors as stem cell regulators, but also obtains stronger cell fate transformation ability than homologous genes of other species. These findings suggest that the aerial root of D. catenatum evolves special structure and developmental characteristics to adapt to epiphytic life, showing high tolerance and dual response to auxin, and DcWOX12 confers cell pluripotency acquisition properties. This research would provide insight into ideal root structure breeding of simulated natural cultivation in D. catenatum and provide a novel target gene for improving the efficiency of monocot plant transformation.